The Mediating Role of Financial Self-Efficacy in Financial Management Behavior - Anggita Nur Reza; Naelati Tubastuvi; Herni Justiana Astuti; Maulida Nurul Innayah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
College students are the agent of change who are expected to boost the country’s economy, but the consumerist and wasteful lifestyle among college students remains a real problem. This study aims to analyze the influence of financial attitude, financial literacy, and locus of control on financial management behavior with financial self-efficacy as a mediating variable among students in Purwokerto. The population in this study consisted of 9,037 active students majoring in economics and business from three universities, namely Muhammadiyah University Purwokerto, Jenderal Soedirman University, and Prof. KH. Saifuddin Zuhri State Islamic University Purwokerto. The sampling technique used the Slovin formula, which produced 170 respondents. The research approach used was quantitative with data processing techniques using SmartPLS version 3.0 through three stages, namely outer model, inner model, and bootstrapping. The results showed that financial attitude, financial literacy, and locus of control had a positive and significant effect on financial self-efficacy and financial management behavior. In addition, financial self-efficacy was also proven to positively and significantly mediate the relationship between financial attitude, financial literacy, and locus of control with financial management behavior. These findings confirm that self-confidence in financial abilities plays an important role in strengthening the relationship between attitude, literacy, and self-control in students' financial management behavior. This study implies that improving financial self-efficacy and financial literacy education should be a primary focus in shaping wise and responsible financial behavior among the younger generation